Ephesians and Artemis the cult of the great goddess of Ephesus as the epistle's context - Immendörfer, Michael 1969-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2017)
Cover -- Preface -- Table of Contents -- List of Tables -- Abbreviations -- Chapter 1: Introduction -- 1.1. Preliminary Remarks -- 1.2. Scope and Aims -- 1.2.1. An Integrated View of Three Topic Areas -- 1.2.1.1. The Letter to the Ephesians -- 1.2.1.2. Ancient Ephesus -- 1.2.1.3. The Church in Ephesus -- 1.2.2. Objective -- 1.3. Methodology -- 1.3.1. Text Comparison -- 1.3.1.1. New Testament References to Jewish Scriptures -- 1.3.1.2. New Testament References to Non-Jewish Texts -- 1.3.2. Definitions and Terminology -- 1.3.2.1. Direct Reference -- 1.3.2.2. Indirect Reference -- 1.3.3. Criteria for Determining Analogies -- 1.3.4. Outline -- Chapter 2: The Recipients of Ephesians -- 2.1. Ephesus and Ephesians: The Present Discussion -- 2.1.1. Monographs on Ephesus: Overview and Comparison -- 2.1.1.1. Studies that Consult Ephesians -- 2.1.1.2. Studies that Refer to Ephesians -- 2.1.1.3. Studies for which Ephesians is not Relevant -- 2.1.1.4. The Monographs' Position on Artemis and Ephesians -- 2.1.2. Commentaries on Ephesians -- 2.1.2.1. The Designation of the Letter -- 2.1.2.2. The Context of Ephesus and Artemis -- 2.1.2.3. The Reception of the Monographs in the Commentaries -- 2.1.3. Summary -- 2.2. Introductory Questions Regarding the Recipients of Ephesians -- 2.2.1. Reception in the Early Church -- 2.2.2. Statements of Ephesians Regarding its Recipients -- 2.2.3. Reasons for and against Ephesian Addressees -- 2.2.3.1. The Absence of ἐν Έφἐơῳ in some Manuscripts -- 2.2.3.2. The Impersonal Nature of the Letter -- 2.3. Summary -- Chapter 3: The City of Ephesus -- 3.1. Sources -- 3.1.1. The Inscriptions of Ephesus -- 3.1.2. Numismatic Sources -- 3.1.3. Texts of Ancient Writers -- 3.1.4. Material in Non-Written Form -- 3.1.5. The Approach of this Research to the Sources -- 3.2. Geography -- 3.3. History -- 3.3.1. The Ionian City.
3.3.2. The Hellenistic City -- 3.3.3. The City of Lysimachus -- 3.3.3.1. Rise -- 3.3.3.2. Golden Age -- 3.3.3.3. Demise -- 3.3.4. The Late Byzantine City -- 3.4. Archaeology -- 3.4.1. The Excavations of British Explorers -- 3.4.2. The Excavations of the Austrian Archaeological Institute -- 3.4.3. Buildings of Special Interest in the Roman Period -- 3.4.3.1. Upper City -- 3.4.3.2. Curetes Street -- 3.4.3.3. Harbour, Commercial and Entertainment Districts -- 3.5. Religions, Magic and Imperial Cult -- 3.5.1. Religions in Ephesus -- 3.5.2. Magic and Έφέơıα Γράμματα -- 3.5.3. Imperial Cult -- 3.6. Summary -- Chapter 4: Artemis Ephesia -- 4.1. The Temple of Artemis -- 4.1.1. History of the Artemision -- 4.1.1.1. Temples A ౼ C and Hekatompedos -- 4.1.1.2. The Temple of Croesus -- 4.1.1.3. The Younger Artemision -- 4.1.2. The Altar of the Artemision -- 4.1.3. Other Functions of the Artemision -- 4.1.3.1. Asylum -- 4.1.3.2. Bank -- 4.1.3.3. Administration of Land -- 4.1.3.4. Mint -- 4.2. The Goddess -- 4.2.1. Origin -- 4.2.2. Cult Figure -- 4.2.2.1. Origin -- 4.2.2.2. Appearance -- 4.2.2.3. Conclusion -- 4.2.3. The Honorific Titles and (Divine) Attributes of Artemis -- 4.2.3.1. Titles in Honour of Artemis -- 4.2.3.2. Artemis' Care for Adherents' Needs -- 4.2.3.3. The Great Name of Artemis -- 4.2.3.4. Arrows as the Main Weapon of Artemis -- 4.2.4. The Bond between Artemis and the City of Ephesus -- 4.2.4.1. Ephesus as the Νεωκόρος of Artemis -- 4.2.4.2. Further Inscriptional Evidence -- 4.3. The Cult of Artemis -- 4.3.1. Processions -- 4.3.2. Festivals -- 4.3.3. The Mysteries of Artemis: Ephesus' Most Important Festival -- 4.4. Summary -- Chapter 5: Ephesians in the Light of Artemis -- 5.1. Analogies in Terms of the Temple of Artemis -- 5.1.1. Building of the Temple -- 5.1.1.1. Building Terminology -- 5.1.1.2. Temple and Temple Building Terminology.
5.1.1.3. Summary -- 5.1.2. The Use of Μέγεθος -- 5.1.3. Sacrifices -- 5.1.4. Wealth and Inheritance -- 5.1.4.1. Wealth -- 5.1.4.2. Inheritance -- 5.2. Analogies in Terms of the Goddess -- 5.2.1. Honorific Titles and Divine Attributes -- 5.2.1.1. Linguistic Similarities -- 5.2.1.2. Analogies to Πρωτοθρουία -- 5.2.2. Taking Care of Needs -- 5.2.3. Thanksgiving -- 5.2.4. Armour -- 5.2.5. Arrows -- 5.2.6. Protection -- 5.2.7. Greatest Name -- 5.2.8. Citizenship, Covenant and Exclusion -- 5.2.8.1. Citizenship -- 5.2.8.2. Covenant -- 5.2.8.3. Exclusion -- 5.2.8.4. Excursus: The Dividing Wall of Hostility -- 5.2.9. The Concept of a Glorious Church/City -- 5.2.10. The Concept of Nurturing -- 5.2.11. Fruit/Fertility -- 5.2.12. Identity -- 5.3. Analogies in Terms of the Cult of Artemis -- 5.3.1. Light and Darkness, Life and Death -- 5.3.1.1. Light and Darkness Terminology in Ephesians -- 5.3.1.2. The Use of Quotations in Ephesians -- 5.3.1.3. Ascent and Descent in Ephesians 4:8 - 10 -- 5.3.1.4. The Quotation in Ephesians 5:14 -- 5.3.1.5. Comparison with the Cult of Artemis -- 5.3.2. Purification -- 5.3.3. Mystery -- 5.3.4. Singing Praises -- 5.3.5. Wine and Debauchery -- 5.4. Excursus: The Cult of Artemis in Other New Testament Books -- 5.4.1. Luke's Narrative of Demetrius' Riot in Acts 19:23 - 41 -- 5.4.2. Paul's Fight with Wild Beasts in 1 Corinthians 15:32 -- 5.4.3. Summary -- 5.5. Evaluation -- 5.5.1. A Body of Knowledge Shared by Author and Readers -- 5.5.1.1. How Well Did Readers in Ephesus Know the Cult of Artemis? -- 5.5.1.2. How Well Did Paul Know the Cult of Artemis? -- 5.5.1.3. Summary -- 5.5.2. The Extent and Clarity of the Artemis Analogies in Ephesians -- 5.5.2.1. Missing Cultic Elements in Ephesians -- 5.5.2.2. Similarities with Regard to Language and Content -- 5.5.2.3. The Cultic Inscriptions in Comparison to Ephesians.
5.5.2.4. Coverage of the Cult of Artemis in Ephesians -- 5.5.2.5. Summary -- 5.5.3. Dissimilarity of Ephesians to Colossians and the Pauline Corpus -- 5.5.3.1. The Hapax Legomena of Ephesians -- 5.5.3.2. Ephesians, Colossians and the Inscriptions of Ephesus -- 5.5.4. Conclusion -- Chapter 6: Ephesians as a Teaching Letter to Former Adherents of Artemis -- 6.1. Ephesians has a Specific Life-Setting -- 6.2. Ephesians is Addressed to Former Adherents of Artemis -- 6.3. Ephesians is a Contextualised Letter -- 6.4. Ephesians is an Authentic Letter -- 6.5. Ephesians as a Source for the Development of the Early Church in Ephesus -- Chapter 7: Overall Conclusion -- Appendixes -- Appendix 1: The Hapax Legomena of Ephesians -- Appendix 2: Common Words of Ephesians and the Inscriptions of Ephesus -- Appendix 3: Literary Testimonies to Artemis, her Cult Figure and Temple -- Appendix 4: Artemis and the Inscriptions of Ephesus -- Appendix 5: Maps -- Appendix 6: Ephesus in Ancient and Modern Times -- Bibliography -- Index of References -- Index of Modern Authors -- Index of Subjects and Places.
Keywords: Artemis -- Göttin; Ephesus (Extinct city)--Religious life and customs; Götter; Ephesus; Hochschulschrift